Comparing Explosive Strength and Speed – Strength in College of Physical Education and Sport Sciences’ Leagues of Basketball and Handball - Kamal, Ali; Mohammed, Bashar; Selam, Karam (Journal of Physical Education, 2020)
The importance of the research lies in identifying differences in some physical abilities of basketball and handball and comparing league players of physical education and sport Sciences College/university of Baghdad. The researchers used the descriptive method on 20 players; (10) basketball players and (10), handball players. The results showed that basketball players are better in legs explosive strength test compared to handball players while handball players were better in arms strength – speed test compared to basketball players.